PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN LEVERAGE KEUANGAN TERHADAP PRAKTIK PERATAAN LABA - Natalia, Irene (Widya Mandala Surabaya Catholic University, 2009)
This research is designed to examine the income smoothing practices in manufactured campanies listed on Ind0i1esia Stock Exchange during 2003-2005, The objectives of this research are examined whether company size, profitability, and financial leverage have significant impact on income smoothing practices, Seventeen listed companies selected using (purposive) judgement sampling method, were used as research sample. Data are analyzed using multiple linear regressions with result that company size and financial leverage have significant impact on income smoothing practices, but hypothesis only supported by financial leverage.